Genetic polymorphisms in ATP1A1 gene and their association with heat tolerance in Jersey crossbred cows By Ramendra Das, I. D. Gupta, Archana Verma, Avtar Singh, Mahesh V Chaudhari, Lalrengpuii Sailo R. C. Upadhyay, J. Goswami - Das, Ramendra (Indian Journal of Dairy Science, 2014)
Global warming and climate change have become the major threat to the sustainability of livestock production systems worldwide. Heat stress produces oxidative stress and affects the alternation of plasma K+ and Na+. In the plasma membrane the ion gradients formed by Na+ - K+-ATPase enzyme is necessary for Na+- coupled transport of metabolites, nutrients and ions and represents a plausible candidate for heat tolerance traits. ATP1A1 gene encodes for α subunit of Na+- K+- ATPase enzyme, has been mapped on BTA 3 and spans about 22.77 kb and includes 23 exons and coding sequence of 3066 nucleotides. The present study was carried out in 35 Jersey crossbred cows with the objectives to identify SNPs in targeted regions (part of exon 16 to intron 18) of ATP1A1 gene and to analyze their association with respiration rate and rectal temperature. A total of five SNPs (A27008223G, T27008097A, C27008016T, G27008015A and C27007790A) were identified in Jersey crossbred cattle. Respiration rate (RR) and rectal temperature (RT) was recorded once during probable extreme hours in winter, spring and summer season. Further, heat tolerance coefficient (HTC) also calculated to see the adaptability of the animals during the period of heat stress. RT in Jersey crossbred cows for AA (38.01±0.16a) and GG (37.86±0.14a) genotype at A27008223G locus did not differ significantly while RR for CA genotype at C27007790A locus was highest (21.76±1.68a) as compared to CC (19.25±1.155b) and AA (16.91±1.57ab) genotypes and HTC for CA genotype at C27007790A locus was highest (1.94±0.07a) as compared to CC (1.83±0.05b) and AA (1.72±0.07ab) genotypes. It is concluded that AA genotype at 27007790 nucleotide position in Jersey crossbred cows were desirable for respiration rate and heat tolerance coefficient respectively.